2021
DOI: 10.1177/11786302211019218
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pitfalls in Wastewater Phosphorus Analysis and How to Avoid Them

Abstract: Due to the increasing adoption of nutrient discharge regulations, many research groups are stepping into new territory with phosphorus (P) measurements. Accurate reporting of P concentrations in effluent from novel wastewater treatment technologies is critical for protecting both environmental and human health. Analysis of P in wastewater is prone to pitfalls because of the (1) variety of chemical forms of P in wastewater (orthophosphate, condensed P, and organic P), (2) availability of different chemical assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…1. There is no standardized and universally accepted approach for classifying the phosphorus fractions and there is urgent need to address this issue along with the standardizing notations of each fraction and corresponding testing method (Rosario et al, 2021). For convenience, TP is generally classified into three major classes i.e.…”
Section: Phosphorus In Wastewater and Its Removal By Treatment Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…1. There is no standardized and universally accepted approach for classifying the phosphorus fractions and there is urgent need to address this issue along with the standardizing notations of each fraction and corresponding testing method (Rosario et al, 2021). For convenience, TP is generally classified into three major classes i.e.…”
Section: Phosphorus In Wastewater and Its Removal By Treatment Processesmentioning
confidence: 99%
“…Therefore, it is recommended to revisit the phosphorus discharge limits and should be ideally based on PO 4 3− concentrations. However, literature review revealed that there is no standardized and globally accepted approach for classifying the phosphorus fractions and this presents an urgent need to address this issue along with the standardized notation of each fraction and corresponding testing method (Rosario et al, 2021). Despite overall effectiveness of different wastewater treatment technologies for TPremoval is well known, there is a dearth of studies documenting the effectiveness of various technologies for removal of specific fractions of phosphorus.…”
Section: Knowledge Gaps and Future Research Directionsmentioning
confidence: 99%
“…Failures in environmental and public health monitoring and measurement, including a discussion on how randomised controlled trials fail to capture the full complexity of WASH interventions within multi-sectoral systems, 10 why better standard procedures are needed for measuring phosphorous in wastewater, 11 how sharing soil testing data through mobile technology is a low priority for farmers in Ghana and Kenya, 12 and how plastic waste from water quality testing creates landfill, but there currently is no reliable method for reusing plastic filtres without impacting on measurement quality 13 ;…”
mentioning
confidence: 99%
“…• • Failures in environmental and public health monitoring and measurement, including a discussion on how randomised controlled trials fail to capture the full complexity of WASH interventions within multi-sectoral systems, 10 why better standard procedures are needed for measuring phosphorous in wastewater, 11 how sharing soil testing data through mobile technology is a low priority for farmers in Ghana and Kenya, 12 and how plastic waste from water quality testing creates landfill, but there currently is no reliable method for reusing plastic filters without impacting on measurement quality 13 ; • • How we can learn from failures in environmental and public health and embed these lessons into our organisations. 14,15 Overall, the papers in this Collection demonstrate that failures happen everywhere: in the laboratory, when engaging with communities, in organisational leadership and even when talking about failure.…”
mentioning
confidence: 99%